Are scrubs really protecting? - Suleman, Fatima (Journal of the Pakistan Medical Association, 2022)
Madam, surgical site infections are a major cause of postoperative morbidity and mortality and have long been a matter of concern. In the early twentieth century, surgeons were allowed to wear their clothes in the operating room (OR). After it was discovered that the surgical attire could be a source of these infections, surgical scrubs were introduced [1]. With the advent of the COVID-19 pandemic, many hospitals changed their policies, requiring healthcare workers to wear scrubs in wards, special care units (SCU), and intensive care units (ICU) due to their encounters with patients. This measure was taken to protect the healthcare personnel from the virus and t ensure that their contaminated clothing did not become a vector of infection to their families and society. The change was quickly adopted particularly in the private sector, due to the free provision of scrubs by the hospital, hospital-laundering facilities, increased comfort and feasibility of the professionals, and most importantly, for the sake of their own and their families’ safety [2]. The issue arose when doctors were observed wearing the same surgical scrubs in the operating room as they did elsewhere in the hospital. Patients admitted at SCU and ICU are infected with multidrug-resistant and extensively drug-resistant microbes, and wearing scrubs contaminated with these organisms in the operating room can be extremely dangerous. Though many hospitals encourage wearing gowns or white coats over the scrubs outside the OR, there is no evidence that it prevents contamination. According to observations and studies, professionals wear white coats even outside the hospital, and are more contaminated by multidrug-resistant organisms. The extent of contamination depends at the type of fabric, antimicrobicidal coating, and the laundering frequency [3]. The national guidelines for infection prevention and control need to be more precise regarding the surgical attire inside and outside the OR, and it should ensure implementation at every hospital. It is suggested that the colour of the scrubs worn inside and outside the OR be different, surgical scrubs should be provided to all healthcare staff by the hospital, and no one should be allowed to wear his personal scrubs inside the hospital. All professionals should be provided lockers, and wearing surgical scrubs outside the hospital should be prohibited. More frequent audits during the pandemic should be done to ensure the safety of the healthcare workers and patients [4].